ANALISIS KLASIFIKASI BEBAN KERJA MENTAL PADA PERAWAT IGD DI RSUP PROF. DR. I.G.N.G NGOERAH - Dr.Ir. I Gusti Ngurah Priambadi. MT; Desak Ayu Sista Dewi. S.TI.M Eng; I Made Dwi Budiana Penindra, MT.; Ni Luh Putu Lilis Sinta Setiawati,S.T ,M.T.; Bryan Estavan Imanuel Sitanggang, S.T.,M.T.; Bagas Karsa, I Gede Bagas Karsa Samadya (Study Program of Industrial Engineering, Udayana University, 2023)
One of the existing problems is the queue at the emergency room of a hospital which is caused by the service to a patient which takes quite a long time so that nurses, doctors, midwives and others are required to work faster. The increased workload of health workers can undoubtedly affect physical and mental changes caused by stress caused by work pressure. The amount of mental workload of nurses at Prof. Hospital. dr. I.G.N.G Ngoerah was assessed using the NASA-TLX method as part of a study on mental workload. The results (NASA - TLX) show that mental workload is high indicating the number of nurses is 26 people, and mental workload is being experienced by 4 nurses in the IGD Prof. Hospital. dr. I.G.N.G Ngoerah. subjective analysis between mental workload and working time and gender mental workload is not affected by gender differences in nurses or the 3 existing work shifts. A further step is to reduce the workload on nurses in the emergency room, such as allocating nurses according to classification and educational background to be more effective in treating patients who have a mental workload under 80.